Dual-frequency VLBI study of Centaurus A on sub-parsec scales The highest-resolution view of an extragalactic jet - Müller, Cornelia; Kadler, Matthias; Roopesh, Ojha; Wilms, Jörn; Böck, Moritz; Edwards, P. G.; Fromm, C. M.; Hase, H.; Horiuchi, S.; Katz, Uli; Lovell, J. E. J.; Ploetz, C.; et al. (Astronomy & Astrophysics, 2011)
Context. Centaurus A is the closest active galactic nucleus. High resolution imaging using Very Long Baseline Interferometry (VLBI) enables us to study the spectral and kinematic behavior of the radio jet-counterjet system on sub-parsec scales, providing essential information for jet emission and formation models.Aims. Our aim is to study the structure and spectral shape of the emission from the central-parsec region of Cen A.Methods. As a target of the Southern Hemisphere VLBI monitoring program TANAMI (Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry), VLBI observations of Cen A are made regularly at 8.4 and 22.3 GHz with the Australian Long Baseline Array (LBA) and associated telescopes in Antarctica, Chile, and South Africa.Results. The first dual-frequency images of this source are presented along with the resulting spectral index map. An angular resolution of 0.4 mas x 0.7 mas is achieved at 8.4 GHz, corresponding to a linear scale of less than 0.013 pc. Hence, we obtain the highest resolution VLBI image of CenA, comparable to previous space-VLBI observations. By combining with the 22.3 GHz image, which has been taken without contributing transoceanic baselines at somewhat lower resolution, we present the corresponding dual-frequency spectral index distribution along the sub-parsec scale jet revealing the putative emission regions for recently detected gamma-rays from the core region by Fermi/LAT.Conclusions. We resolve the innermost structure of the milliarcsecond scale jet and counterjet system of CenA into discrete components. The simultaneous observations at two frequencies provide the highest resolved spectral index map of an AGN jet allowing us to identify multiple possible sites as the origin of the high energy emission.
Keywords: techniques: high angular resolution; galaxies: individual: Centaurus A; black hole physics; galaxies: active; galaxies: individual: NGC 5128; galaxies: jets

Investigating source confusion in PMN J1603-4904 - Krauss, F.; Kreter, M.; Mueller, C.; Markowitz, A.; Böck, Moritz; Burnett, T.; Dauser, Thomas; Kadler, M.; Kreikenbohm, A.; Ojha, R.; Wilms, Jörn (Astronomy & Astrophysics, 2018)
PMN J1603-4904 is a likely member of the rare class of gamma-ray emitting young radio galaxies. Only one other source, PKS 1718-649, has been confirmed so far. These objects, which may transition into larger radio galaxies, are a stepping stone to understanding AGN evolution. It is not completely clear how these young galaxies, seen edge-on, can produce high-energy gamma rays. PMN J1603-4904 has been detected by TANAMI Very Long Baseline Interferometry (VLBI) observations and has been followed-up with multiwavelength observations. A Fermi Gamma-ray Space Telescope Large Area Telescope (Fermi-LAT) gamma-ray source has been associated with this young galaxy in the LAT catalogs. We have obtained Chandra observations of the source to consider the possibility of source confusion due to the relatively large positional uncertainty of Fermi-LAT. The goal was to investigate the possibility of other X-ray bright sources in the vicinity of PMN J1603-4904 that could be counterparts to the gamma-ray emission. With Chandra/ACIS, we find no other sources in the uncertainty ellipse of Fermi-LAT data, which includes an improved localization analysis of eight years of data. We further study the X-ray fluxes and spectra. We conclude that PMN J1603-4904 is indeed the second confirmed gamma-ray bright young radio galaxy.
Keywords: galaxies: active; galaxies: jets; Galaxy: abundances; galaxies: individual: PMN J1603-4904

Irradiation of an accretion disc by a jet: general properties and implications for spin measurements of black holes - Dauser, Thomas; Garcia, Javier; Wilms, Jörn; Böck, Moritz; Brenneman, L. W.; Falanga, M.; Fukumura, K.; Reynolds, C. S. (Monthly Notices of the Royal Astronomical Society, 2013)
X-ray irradiation of the accretion disc leads to strong reflection features, which are then broadened and distorted by relativistic effects. We present a detailed, general relativistic approach to model this irradiation for different geometries of the primary X-ray source. These geometries include the standard point source on the rotational axis as well as more jet-like sources, which are radially elongated and accelerating. Incorporating this code in the RELLINE model for relativistic line emission, the line shape for any configuration can be predicted. We study how different irradiation geometries affect the determination of the spin of the black hole. Broad emission lines are produced only for compact irradiating sources situated close to the black hole. This is the only case where the black hole spin can be unambiguously determined. In all other cases the line shape is narrower, which could either be explained by a low spin or an elongated source. We conclude that in those cases and independent of the quality of the data no unique solution for the spin exists and therefore only a lower limit of the spin value can be given.
Keywords: accretion; accretion discs; black hole physics; lines: profiles; galaxies: active; galaxies: nuclei

Long term variability of Cygnus X-1 VII. Orbital variability of the focussed wind in Cyg X-1/HDE 226868 system - Grinberg, V.; Leutenegger, M. A.; Hell, Natalie; Pottschmidt, K.; Böck, Moritz; Garcia, J. A.; Hanke, Manfred; Nowak, M. A.; Sundqvist, J. O.; Townsend, R. H. D.; Wilms, Jörn (Astronomy & Astrophysics, 2015)
Binary systems with an accreting compact object off er a unique opportunity to investigate the strong, clumpy, line-driven winds of early-type supergiants by using the compact object's X-rays to probe the wind structure. We analyze the two-component wind of HDE 226868, the O9.7Iab giant companion of the black hole Cyg X-1, using 4.77 Ms Rossi X-ray Timing Explorer (RXTE) observations of the system taken over the course of 16 years. Absorption changes strongly over the 5.6 d binary orbit, but also shows a large scatter at a given orbital phase, especially at superior conjunction. The orbital variability is most prominent when the black hole is in the hard X-ray state. Our data are poorer for the intermediate and soft state, but show signs for orbital variability of the absorption column in the intermediate state. We quantitatively compare the data in the hard state to a toy model of a focussed Castor-Abbott-Klein wind: as it does not incorporate clumping, the model does not describe the observations well. A qualitative comparison to a simplified simulation of clumpy winds with spherical clumps shows good agreement in the distribution of the equivalent hydrogen column density for models with a porosity length on the order of the stellar radius at inferior conjunction; we conjecture that the deviations between data and model at superior conjunction could either be due to lack of a focussed wind component in the model or to a more complicated clump structure.
Keywords: stars: individual: Cyg X-1; X-rays: binaries; binaries : close; stars: winds; outflows

Spectro-timing analysis of Cygnus X-1 during a fast state transition - Böck, Moritz; Grinberg, Victoria; Pottschmidt, K.; Hanke, Manfred; Nowak, M. A.; Markoff, S. B.; Uttley, P.; Rodriguez, Jerome; Pooley, G. G.; Suchy, S.; Rothschild, R. E.; Wilms, Jörn (Astronomy & Astrophysics, 2011)
We present the analysis of two long, quasi-uninterrupted RXTE observations of Cygnus X-1 that span several days within a 10 d interval. The spectral characteristics during this observation cover the region where previous observations have shown the source to be most dynamic. Despite that the source behavior on time scales of hours and days is remarkably similar to that on year time scales. This includes a variety of spectral/temporal correlations that previously had only been observed over CygX-1's long-term evolution. Furthermore, we observe a full transition from a hard to a soft spectral state that occurs within less than 2.5 h - shorter than previously reported for any other similar CygX-1 transition. We describe the spectra with a phenomenological model dominated by a broken power law, and we fit the X-ray variability power spectra with a combination of a cutoff power law and Lorentzian components. The spectral and timing properties are correlated: the power spectrum Lorentzian components have an energy-dependent amplitude, and their peak frequencies increase with photon spectral index. Averaged over 3.2-10 Hz, the time lag between the variability in the 4.5-5.7 keV and 9.5-15 keV bands increases with decreasing hardness when the variability is dominated by the Lorentzian components during the hard state. The lag is small when there is a large power law noise contribution, shortly after the transition to the soft state. Interestingly, the soft state not only shows the shortest lags, but also the longest lags when the spectrum is at its softest and faintest. We discuss our results in terms of emission models for black hole binaries.
Keywords: X-rays: binaries; X-rays: individuals: CygX-1

TANAMI: Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry - Mueller, C.; Kadler, M.; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Ros, E.; Carpenter, B.; Angioni, R.; Blanchard, J.; Böck, Moritz; Burd, P. R.; et al. (Astronomy & Astrophysics, 2018)
Context. TANAMI is a multiwavelength program monitoring active galactic nuclei (AGN) south of -30 degrees declination including high-resolution very long baseline interferometry (VLBI) imaging, radio, optical/UV, X-ray, and gamma-ray studies. We have previously published first-epoch 8.4 GHz VLBI images of the parsec-scale structure of the initial sample. In this paper, we present images of 39 additional sources. The full sample comprises most of the radio-and gamma-ray brightest AGN in the southern quarter of the sky, overlapping with the region from which high-energy (>100 TeV) neutrino events have been found.Aims. We characterize the parsec-scale radio properties of the jets and compare them with the quasi-simultaneous Fermi/LAT gamma-ray data. Furthermore, we study the jet properties of sources which are in positional coincidence with high-energy neutrino events compared to the full sample. We test the positional agreement of high-energy neutrino events with various AGN samples.Methods. TANAMI VLBI observations at 8.4 GHz are made with southern hemisphere radio telescopes located in Australia, Antarctica, Chile, New Zealand, and South Africa.Results. Our observations yield the first images of many jets below -30 degrees declination at milliarcsecond resolution. We find that gamma-ray loud TANAMI sources tend to be more compact on parsec-scales and have higher core brightness temperatures than gamma-ray faint jets, indicating higher Doppler factors. No significant structural difference is found between sources in positional coincidence with high-energy neutrino events and other TANAMI jets. The 22 gamma-ray brightest AGN in the TANAMI sky show only a weak positional agreement with high-energy neutrinos demonstrating that the >100 TeV IceCube signal is not simply dominated by a small number of the gamma-ray brightest blazars. Instead, a larger number of sources have to contribute to the signal with each individual source having only a small Poisson probability for producing an event in multi-year integrations of current neutrino detectors.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; radio continuum: galaxies; techniques: high angular resolution; neutrinos

TANAMI: tracking active galactic nuclei with austral milliarcsecond interferometry I. First-epoch 8.4GHz images - Ojha, R.; Kadler, Matthias; Böck, Moritz; Booth, R.; Dutka, M. S.; Edwards, P. G.; Fey, A. L.; Fuhrmann, L.; Gaume, R. A.; Hase, H.; Horiuchi, S.; Jauncey, D. L.; et al. (Astronomy & Astrophysics, 2010)
Context. A number of theoretical models vie to explain the gamma-ray emission from active galactic nuclei (AGN). This was a key discovery of EGRET. With its broader energy coverage, higher resolution, wider field of view and greater sensitivity, the Large Area Telescope (LAT) of the Fermi Gamma-ray Space Telescope is dramatically increasing our knowledge of AGN gamma-ray emission. However, discriminating between competing theoretical models requires quasi-simultaneous observations across the electromagnetic spectrum. By resolving the powerful parsec-scale relativistic outflows in extragalactic jets and thereby allowing us to measure critical physical properties, Very Long Baseline Interferometry observations are crucial to understanding the physics of extragalactic gamma-ray objects.Aims. We introduce the TANAMI program (Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry) which is monitoring an initial sample of 43 extragalactic jets located south of -30 degrees declination at 8.4GHz and 22GHz since 2007. All aspects of the program are discussed. First epoch results at 8.4GHz are presented along with physical parameters derived therefrom.Methods. These observations were made during 2007/2008 using the telescopes of the Australian Long Baseline Array in conjunction with Hartebeesthoek in South Africa. These data were correlated at the Swinburne University correlator.Results. We present first epoch images for 43 sources, some observed for the first time at milliarcsecond resolution. Parameters of these images as well as physical parameters derived from them are also presented and discussed. These and subsequent images from the TANAMI survey are available at http://pulsar.sternwarte.uni-erlangen.de/tanami/.Conclusions. We obtain reliable, high dynamic range images of the southern hemisphere AGN. All the quasars and BL Lac objects in the sample have a single-sided radio morphology. Galaxies are either double-sided, single-sided or irregular. About 28% of the TANAMI sample has been detected by LAT during its first three months of operations. Initial analysis suggests that when galaxies are excluded, sources detected by LAT have larger opening angles than those not detected by LAT. Brightness temperatures of LAT detections and non-detections seem to have similar distributions. The redshift distributions of the TANAMI sample and sub-samples are similar to those seen for the bright gamma-ray AGN seen by LAT and EGRET but none of the sources with a redshift above 1.8 have been detected by LAT.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; gamma rays: observations; quasars: general

The causal connection between disc and power-law variability in hard state black hole X-ray binaries - Uttley, P.; Wilkinson, T.; Cassatella, P.; Wilms, Jörn; Pottschmidt, K.; Hanke, Manfred; Böck, Moritz (Monthly Notices of the Royal Astronomical Society, 2011)
We use the XMM-Newton EPIC-pn instrument in timing mode to extend spectral time-lag studies of hard state black hole X-ray binaries into the soft X-ray band. We show that variations of the disc blackbody emission substantially lead variations in the power-law emission, by tenths of a second on variability time-scales of seconds or longer. The large lags cannot be explained by Compton scattering but are consistent with time delays due to viscous propagation of mass accretion fluctuations in the disc. However, on time-scales less than a second the disc lags the power-law variations by a few milliseconds, consistent with the disc variations being dominated by X-ray heating by the power law, with the short lag corresponding to the light traveltime between the power-law emitting region and the disc. Our results indicate that instabilities in the accretion disc are responsible for continuum variability on time-scales of seconds or longer and probably also on shorter time-scales.
Keywords: accretion; accretion discs; X-rays: binaries; X-rays: individual: GX 339-4